Dynamic and secure remote database access with soft access policies integration - Regateiro, Diogo José Domingues (2021)
The amount of data being created and shared has grown greatly in recent years, thanks in part to social media and the growth of smart devices. Managing the storage and processing of this data can give a competitive edge when used to create new services, to enhance targeted advertising, etc. To achieve this, the data must be accessed and processed. When applications that access this data are developed, tools such as Java Database Connectivity, ADO.NET and Hibernate are typically used. However, while these tools aim to bridge the gap between databases and the object-oriented programming paradigm, they focus only on the connectivity issue. This leads to increased development time as developers need to master the access policies to write correct queries. Moreover, when used in database applications within noncontrolled environments, other issues emerge such as database credentials theft; application authentication; authorization and auditing of large groups of new users seeking access to data, potentially with vague requirements; network eavesdropping for data and credential disclosure; impersonating database servers for data modification; application tampering for unrestricted database access and data disclosure; etc. Therefore, an architecture capable of addressing these issues is necessary to build a reliable set of access control solutions to expand and simplify the application scenarios of access control systems. The objective, then, is to secure the remote access to databases, since database applications may be used in hard-to-control environments and physical access to the host machines/network may not be always protected. Furthermore, the authorization process should dynamically grant the appropriate permissions to users that have not been explicitly authorized to handle large groups seeking access to data. This includes scenarios where the definition of the access requirements is difficult due to their vagueness, usually requiring a security expert to authorize each user individually. This is achieved by integrating and auditing soft access policies based on fuzzy set theory in the access control decision-making process. A proof-of-concept of this architecture is provided alongside a functional and performance assessment.